Honey and spice eaudiobook A novel. - Babalola, Bolu (HarperAudio, 2022)
INSTANT NATIONAL BESTSELLER A REESE'S BOOK CLUB PICK A TIKTOK BOOK CLUB PICK ""Sexy, messy and wry, Honey and Spice more than delivers."" — New York Times Book Review ""A vibrant debut novel . . . Babalola is incisively funny, capturing the kick and sweetness of her title with her words."" — Entertainment Weekly Named a Best Book of the Year by Time Esquire Vanity Fair Oprah Daily Cosmopolitan Elle Harper's Bazaar Southern Living Buzzfeed Women's Health Magazine AudioFile Popsugar and more! Introducing internationally bestselling author Bolu Babalola's dazzling debut novel, full of passion, humor, and heart, that centers on a young Black British woman who has no interest in love and unexpectedly finds herself caught up in a fake relationship with the man she warned her girls about Sweet like plantain, hot like pepper. They taste the best when together... Sharp-tongued (and secretly soft-hearted) Kiki Banjo has just made a huge mistake. As an expert in relationship-evasion and the host of the popular student radio show Brown Sugar, she's made it her mission to make sure the women of the African-Caribbean Society at Whitewell University do not fall into the mess of "situationships", players, and heartbreak. But when the Queen of the Unbothered kisses Malakai Korede, the guy she just publicly denounced as "The Wastemen of Whitewell," in front of every Blackwellian on campus, she finds her show on the brink. They're soon embroiled in a fake relationship to try and salvage their reputations and save their futures. Kiki has never surrendered her heart before, and a player like Malakai won't be the one to change that, no matter how charming he is or how electric their connection feels. But surprisingly entertaining study sessions and intimate, late-night talks at old-fashioned diners force Kiki to look beyond her own presumptions. Is she ready to open herself up to something deeper? A gloriously funny and sparkling debut novel, Honey and Spice is full of delicious tension and romantic intrigue that will make you weak at the knees. ""A smart, sexy summer read, which hits your brain and your romance buttons in one shot."" — Los Angeles Times ""The ultimate summer romance . . . It's got all the juiciest, most satisfying romance tropes, but in Babalola's capable hands, the story feels fresh and unique."" — The Cut, New York magazine "Divine summer reading. Hilarious, hot, and heartfelt. " — Meg Cabot, #1 New York Times bestselling author